RNA sequencing of early round goby embryos reveals that maternal experiences can shape the maternal RNA contribution in a wild vertebrate - Adrian-Kalchhauser, Irene (BMC Evol Biol, 2018)
BACKGROUND: It has been proposed that non-genetic inheritance could promote species fitness. Non-genetic inheritance could allow offspring to benefit from the experience of their parents, and could advocate pre-adaptation to prevailing and potentially selective conditions. Indeed, adaptive parental effects have been modeled and observed, but the molecular mechanisms behind them are far from understood. RESULTS: In the present study, we investigated whether maternal RNA can carry information about environmental conditions experienced by the mother in a wild vertebrate. Maternal RNA directs the development of the early embryo in many non-mammalian vertebrates and invertebrates. However, it is not known whether vertebrate maternal RNA integrates information about the parental environment. We sequenced the maternal RNA contribution from a model that we expected to rely on parental effects: the invasive benthic fish species Neogobius melanostomus (Round Goby). We found that maternal RNA expression levels correlated with the water temperature experienced by the mother before oviposition, and identified temperature-responsive gene groups such as core nucleosome components or the microtubule cytoskeleton. CONCLUSIONS: Our findings suggest that the maternal RNA contribution may incorporate environmental information. Maternal RNA should therefore be considered a potentially relevant pathway for non-genetic inheritance. Also, the ability of a species to integrate environmental information in the maternal RNA contribution could potentially contribute to species fitness and may also play a role in extraordinary adaptive success stories of invasive species such as the round goby. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12862-018-1132-2) contains supplementary material, which is available to authorized users.